LEGISLATION AND SOCIAL AWARENESS IN TRAFFIC: PATHWAYS TO REDUCING ACCIDENTS AND PROMOTING WELL-BEING (CIPEEX, 2025)
This study adopts an interdisciplinary perspective to examine traffic accidents, addressing their sociological and legal implications. The focus is on analyzing necessary conduct from both sociological thinkers' viewpoints and Brazilian normative guidelines to promote a broader understanding of the topic. The proposal discusses required daily conduct from a sociological and legal perspective, emphasizing the importance of good faith in resolving contemporary conflicts. Referenced authors ground an introduction to social studies and Law, aiming to explore the theme accessibly. The analysis serves as an introductory basis for understanding the issues addressed. The study also highlights intersections between Civil and Penal Law, particularly regarding omissions and illicit conduct under the Penal Code, with emphasis on traffic offenses. This work has a didactic character, seeking to inform the population extensionally, expositorily, and guidingly about appropriate conduct and ensured rights.
Keywords: Traffic Accident; Law; Sociology; Conduct